The importance of inter-religious dialogue to promote world peace: a Buddhist perspective - Poey, Tiang Peow (DR. Poet Tiang Peow, 2009)

(untitled)
At the dawn of the 21st century, interfaith-religious dialogue plays a central role in public life and has become one of the best platforms and channels to promote world peace. At this juncture, analyzing and synthesizing the sequencing stages of belief, understanding, practice, and realization from a Buddhist perspective towards the importance of interfaith-religious dialogue to promote world peace is a timely, necessary, expedient and a long term undertaking.